Особливості адміністративної відповідальності у сфері контролю за обігом лікарських засобів - Миронюк, Р. В.; Myroniuk, R. V.; Моргунов, О. А.; Morgunov, O. A.; ORCID: http://orcid.org/0000-0003-2259-3620 (Юридичний науковий електронний журнал. - 2023. - № 2. - С. 340-343, 2023)
З’ясовано види адміністративних правопорушень у сфері обігу лікарських препаратів в Україні, виокремлено особливості застосування заходів адміністративної відповідальності за порушення у цій сфері та запропоновано окремі шляхи удосконалення правових засад встановлення та реалізації адміністративної відповідальності у цій сфері. Здійснено аналіз складів адміністративних правопорушень у сфері обігу лікарських препаратів в Україні, запропоновано здійснити їх поділ на такі види: правопорушення у сфері реалізації лікарських засобів; правопорушення у сфері реалізації контролю за обігом лікарських засобів; правопорушення у сфері легалізації лікарських засобів. Визначено рівень правового забезпечення відповідальності у сфері контролю за обігом лікарських засобів, виявлено прогалини в цій сфері та обґрунтовано напрямки удосконалення адміністративно-деліктного законодавства у цій сфері.

In order to fulfill the tasks of the research, an attempt was made to solve the following tasks: to find out the types of administrative offenses in the sphere of circulation of medicinal products in Ukraine, to single out the features of the application of measures of administrative responsibility for violations in this area, and to propose separate ways of improving the legal basis for establishing and implementing administrative responsibility in this area. An analysis of the composition of administrative offenses in the sphere of circulation of medicinal products in Ukraine was carried out, and it was proposed to divide them into the following types: offenses in the sphere of sale of medicinal products; offenses in the field of implementation of control over the circulation of medicinal products; offenses in the field of legalization of medicinal products. The level of legal protection of responsibility in the field of control over the circulation of medicinal products has been determined, gaps in this field have been identified, and directions for improving the administrative and tort legislation in this field have been substantiated. In particular, it has been proven that it is expedient to expand the disposition of Article 42-4 of the Code of Administrative Offenses «Violation of the established procedure for the sale (issuance) of medicinal products» and to establish effective measures of administrative responsibility for their commission. It is proposed to establish administrative responsibility for the following violations: dispensing without a doctor’s prescription of combined medicinal products containing codeine and other controlled substances; implementation in any way, including online trading of biological supplements that are not medicinal products that have not been certified in accordance with the procedure established by law. It is suggested that the authority to file case files on such offenses should be left to the State Medical Service, in accordance with Article 244-8 of the Code of Administrative Offenses, and the right to review case files on such offenses should be transferred from the State Medical Service to district, city district, city or city district courts, in accordance with Article 221 of the Code of Administrative Offenses .

Выяснены виды административных правонарушений в сфере обращения лекарственных препаратов в Украине, выделены особенности применения мер административной ответственности за нарушение в этой сфере и предложены отдельные пути усовершенствования правовых основ установления и реализации административной ответственности в этой сфере.
Peculiarities of administrative responsibility in the field of control over the circulation of medicinal products
Миронюк, Р. В. Особливості адміністративної відповідальності у сфері контролю за обігом лікарських засобів [Електронний ресурс] / Миронюк Р. В., Моргунов О. А. // Юридичний науковий електронний журнал. - 2023. - № 2. - С. 340-343. – Режим доступу: http://www.lsej.org.ua/2_2023/79.pdf.
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; контроль за обігом лікарських засобів; control over the circulation of medicinal products; контроль за оборотом лекарственных средств; Державна служба України з лікарських засобів та контролю за наркотиками; State Service of Ukraine for Medicinal Products and Control of drugs; Государственная служба Украины по лекарственным средствам и контролю за наркотиками; адміністративна відповідальність; administrative responsibility; административная ответственность; адміністративні правопорушення; administrative offenses; административные правонарушения; правове забезпечення; legal support; правовое обеспечение